MONITORING FILTER PADA TANGKI AIR MENGGUNAKAN SENSOR TURBIDITY BERBASIS ARDUINO MEGA 2560 VIA SMS GATEWAY - faizal Fatturahman; Irawan Irawan (Universitas Lampung, 2019)
Clean water has a very important role in human life. If an area is difficult to get clean water for daily needs, then they have to buy water to get it. Based on these problems, research was carried out in the form of a filter tool that can be used to filter turbid water into clean water so that it can be used for daily needs and can be monitored in real-time. To be able to make these tools requires software to program so that all hardware can run, the components used are electronic components consisting of an Arduino Mega 2560, HC-SR04 Sensor, Turbidity Sensor, SIM 800L, Waterpump, and a simple water filter as a compliment. This tool works automatically, when the water tank is full of clean water, the user will receive a notification in the form of an SMS. It is hoped that the existence of this tool can help to get clean and healthy water for daily needs.